How tall buildings affect turbulent air flows and dispersion of pollution within a neighbourhood. (February 2018) - Aristodemou, Elsa; Boganegra, Luz Maria; Mottet, Laetitia; Pavlidis, Dimitrios; Constantinou, Achilleas; Pain, Christopher; Robins, Alan; ApSimon, Helen
Abstract: The city of London, UK, has seen in recent years an increase in the number of high-rise/multi-storey buildings ("skyscrapers") with roof heights reaching 150 m and more, with the Shard being a prime example with a height of ∼310 m. This changing cityscape together with recent plans of local authorities of introducing Combined Heat and Power Plant (CHP) led to a detailed study in which CFD and wind tunnel studies were carried out to assess the effect of such high-rise buildings on the dispersion of air pollution in their vicinity. A new, open-source simulator, FLUIDITY, which incorporates the Large Eddy Simulation (LES) method, was implemented; the simulated results were subsequently validated against experimental measurements from the EnFlo wind tunnel. The novelty of the LES methodology within FLUIDITY is based on the combination of an adaptive, unstructured, mesh with an eddy-viscosity tensor (for the sub-grid scales) that is anisotropic. The simulated normalised mean concentrations results were compared to the corresponding wind tunnel measurements, showing for most detector locations good correlations, with differences ranging from 3% to 37%. The validation procedure was followed by the simulation of two further hypothetical scenarios, in which the heights of buildings surrounding the source building were increased. The results showed clearly how the high-rise buildings affected the surrounding air flows and dispersion patterns, with the generation of "dead-zones" and high-concentration "hotspots" in areas where these did not previously exist. The work clearly showed that complex CFD modelling can provide useful information to urban planners when changes to cityscapes are considered, so that design options can be tested against environmental quality criteria. Graphical abstract: Image 1 Highlights: Validation of novel LES model, using an adaptive, anisotropic eddy viscosity model. Effect of tall buildings on velocity as well as pollution concentration fields is clearly seen. Presence of tall buildings leads to pollution remaining locally within the building area. Location and extend of newly-formed concentration hotspots depend on the height of the tall buildings surrounding the "source" building. Abstract : This study shows how the presence of tall buildings affects the dispersion of air pollutants within a small neighbourhood, and how concentration hotspots can be generated in areas which were previously pollution-free.